Synergistic Anti-inflammatory and Neuroprotective Effects of Cinnamomum cassia and Zingiber officinale Alleviate Diabetes-Induced Hippocampal Changes in Male Albino Rats: Structural and Molecular Evidence - ALmohaimeed, Hailah M.; Mohammedsaleh, Zuhair M.; Batawi, Ashwaq H.; Balgoon, Maha Jameal; Ramadan, Osama Ibrahim; Baz, Hasan Ahmed; Al Jaouni, Soad; Ayuob, Nasra Naeim (Frontiers in Cell and Developmental Biology, 2021)
Background: Although ginger and cinnamon have neuroprotective properties, their capacity to inhibit neuroinflammation, when administrated together, has not been investigated. Objectives: This study aimed to assess the synergistic effect of Cinnamomum cassia and Zingiber officinale on regulating blood glucose, improving hippocampal structural changes and depressive-like alternations in diabetic rats and to explore the mechanism behind this effect. Material and methods: Thirty male Spraque-Dawley rats were divided into equal 5 groups (n=6); the normal control, untreated streptozotocin (STZ)-diabetic, cinnamon-treated diabetic (100 mg/kg of body weight/day for 6 weeks), ginger-treated diabetic (500 mg/kg body weight/day for 6 weeks) and ginger plus cinnamon-treated diabetic groups. Forced swim test (FST) and elevated plus maze (EPM) behavioral tests were performed at the end of the experiment. HOMA-IR, HOMA β-cells, blood glucose, insulin, corticosterone, pro-inflammatory cytokines tumor necrosis factor-α (TNF-α) and IL-6) and total anti-oxidant capacity (TAC) were assessed in the serum. BDNF mRNA level was assessed in hippocampus using qRT-PCR. Hippocampal histopathological changes were also assessed. Results: Diabetes-induced depressive-like changes were biochemically confirmed in STZ group, as serum corticosterone level significantly (p< 0.001) increased, as well as behaviorally using FST and EPM tests. DM induced degenerative changes in the hippocampus. Treatment of diabetic rats with ginger, cinnamon or the combination of them alleviated these pathological changes and significantly increased (p<0.001) hippocampal BDNF gene expression, ki67 hippocampal immunoexpression serum insulin, TAC, while they significantly reduced serum levels of blood glucose, IL-6, TNF-α, IL1β as well as GFAP and caspase-3 hippocampal immunoexpression compared to the untreated diabetic groups. Improvement induced by the combination of ginger and cinnamon was superior to the single treatment with either of them. In conclusion: Cinnamomum cassia and Zingiber officinale have a synergistic hypoglycemic, antioxidant, anti-inflammatory, antidepressant-like and neuroprotective effects.